Asymmetric Membranes from Two Chemically Distinct Triblock Terpolymers Blended during Standard Membrane Fabrication. Issue 20 (8th September 2016) - Li, Yuk Mun; Srinivasan, Divya; Vaidya, Parth; Gu, Yibei; Wiesner, Ulrich
Abstract : Deviating from the traditional formation of block copolymer derived isoporous membranes from one block copolymer chemistry, here asymmetric membranes with isoporous surface structure are derived from two chemically distinct block copolymers blended during standard membrane fabrication. As a first proof of principle, the fabrication of asymmetric membranes is reported, which are blended from two chemically distinct triblock terpolymers, poly(isoprene‐ b ‐styrene‐ b ‐(4‐vinyl)pyridine) (ISV) and poly(isoprene‐ b ‐styrene‐ b ‐(dimethylamino)ethyl methacrylate) (ISA), differing in the pH‐responsive hydrophilic segment. Using block copolymer self‐assembly and nonsolvent induced phase separation process, pure and blended membranes are prepared by varying weight ratios of ISV to ISA. Pure and blended membranes exhibit a thin, selective layer of pores above a macroporous substructure. Observed permeabilities at varying pH values of blended membranes depend on relative triblock terpolymer composition. These results open a new direction for membrane fabrication through the use of mixtures of chemically distinct block copolymers enabling the tailoring of membrane surface chemistries and functionalities. Abstract : Asymmetric membranes with isoporous surface structures are derived from two chemically distinct triblock terpolymers blended during the standard membrane fabrication process. Through block copolymer self‐assembly and nonsolvent induced phase separation, blended ultrafiltration membranes from varying ratios of poly(isoprene‐ b ‐styrene‐ b ‐(4‐vinyl)pyridine) and poly(isoprene‐ b ‐styrene‐ b ‐(dimethylamino)ethyl methacryate) enable the tailoring of pore surface chemistries and resulting membrane properties.